Fumigant and Repellent Activities of Different Essential Oils Alone and Combined Against the Maize Weevil (Sitophilus Zeamais Motschulsky) - Arena, Julieta Soledad (2017)
The insecticidal and repellent activity of five essential oils (EOs) was studied separately and in binary combinations against Sitophilus zeamais. Minthostachys verticillata EO showed the highest fumigant activity with a LC50 value of 28.2 μl/l air. A moderate toxicity was observed with Eucalyptus globulus EO (LC50 = 335.7 μl/l air), whereas the EOs from Aloysia citriodora, Coriandrum sativum and Mentha sp. did not show insecticidal effect at 600 μl/l air. All combinations that include M. verticillata EO showed strong fumigant activity with LC50 values lesser than 78 μl/l air. The co-toxicity coefficient (CCT) of M. verticillata and E. globulus EO combination indicating an aditive effect (CTC = 119.1). Repellent activity was evaluated using two-choice olfactometer assay. All EOs and their combinations had repellent effect on adults of S. zeamais (P < 0.05).